2020
DOI: 10.31234/osf.io/mqpvn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and Student Well-being: Stress and Mental Health during Return-to-School

Abstract: Students have been multiply impacted by the COVID-19 pandemic: threats to their own and their family’s health, the closure of schools, and pivoting to online learning in March 2020, a long summer of physical distancing, and then the challenge of returning to school in fall 2020. As damaging as the physical health effects of a global pandemic are, much has been speculated about the “second wave” of mental health crises, particularly for school-aged children and adolescents. Yet, few studies have asked students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…In addition, adolescents had returned to school by the time we conducted the survey, whereas young adults were still at home. As COVID-19 can PTSD NETWORK COMPARISON ACROSS AGE 5 transmit from person to person, adolescents spending time in crowded classrooms would naturally exhibit greater fear and anxiety of being infected, which explains the influence of the exaggerated startle response (Schwartz et al, 2021).…”
Section: Sun and Zhoumentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, adolescents had returned to school by the time we conducted the survey, whereas young adults were still at home. As COVID-19 can PTSD NETWORK COMPARISON ACROSS AGE 5 transmit from person to person, adolescents spending time in crowded classrooms would naturally exhibit greater fear and anxiety of being infected, which explains the influence of the exaggerated startle response (Schwartz et al, 2021).…”
Section: Sun and Zhoumentioning
confidence: 99%
“…transmit from person to person, adolescents spending time in crowded classrooms would naturally exhibit greater fear and anxiety of being infected, which explains the influence of the exaggerated startle response (Schwartz et al, 2021).…”
Section: S33mentioning
confidence: 99%
“…For example, in Zhou et als' (2020) cross-sectional study of 8079 Chinese students aged 12-18 years, over one-third of the sampled population was experiencing depressive symptoms, anxiety symptoms, or a combination of both. Similarly, Schwartz et al (2021) online survey of over 2000 12-18-year-old Alberta students found that 25% of participants were experiencing stress levels above critical thresholds and that these stress levels were significantly correlated to behavioral difficulties, such as inattention, sleep problems, and negative affect. These findings point to a need to attend to the mental health status of the adolescent population and underscore the importance of psychological wellbeing during the pandemic.…”
mentioning
confidence: 99%
“…A partir de ello, Salaverra y Usan (2017), sugieren que el modo de manejo de un determinado conflicto reside en el enfoque en el problema, más no en el individuo que lo experimenta; por otro lado, a este estilo de afrontamiento se le denominó no productivo, debido a que no promovía ningún tipo de motivación a la solución. Esto sigue, la importancia de los programas colectivos o a través de un especialista capacitado que dirige a los adolescentes en el enfoque del concepto de sí mismos, la revaluación de las fortalezas, la gestión del afecto negativo y la estrategia para resolver problemas (Arias, 2017;Schwartz et al, 2021). Asimismo, en relación a la influencia de la ansiedad y la depresión sobre la focalización del problema (p<.05; Exp[B]=.896), donde en base a los resultados obtenidos, el modelo propuesto explica el 10% de la relación entre la variable predictora sobre la focalización del problema.…”
Section: Discussionunclassified
“…No obstante, Schwartz et al (2021) precisa la importancia de la gestión de las emociones que presentan las personas con síntomas depresivos, con el objetivo de contrarrestar los efectos negativos que se relacionan a trastornos psicológicos. Por otro lado, en cuanto a la influencia de la depresión y ansiedad sobre el estilo de afrontamiento basado en el fatalismo está relacionado a la religión y/o espiritualidad, por lo que se puede decir, que los adolescentes toman posturas relacionadas a la religión como apoyo social frente a contextos negativos (González et al, 2018).…”
Section: Discussionunclassified